Natural compounds isolated from Brazilian plants are potent inhibitors of hepatitis C virus replication in vitro - Jardim, Ana Carolina Gomes [UNESP]; Igloi, Zsofia; Shimizu, Jacqueline Farinha [UNESP]; Santos, Vania Aparecida de Freitas Formenton Macedo dos [UNESP]; Felippe, Lidiane Gaspareto [UNESP]; Mazzeu, Bruna Fonseca [UNESP]; Amako, Yutaka; Furlan, Maysa [UNESP]; Harris, Mark; Rahal, Paula [UNESP] (My University, 2014)
Compounds extracted from plants can provide an alternative approach to new therapies. They present characteristics such as high chemical diversity, lower cost of production and milder or inexistent side effects compared with conventional treatment. The Brazilian flora represents a vast, largely untapped, resource of potential antiviral compounds. In this study, we investigate the antiviral effects of a panel of natural compounds isolated from Brazilian plants species on hepatitis C virus (HCV) genome replication. To do this we used firefly luciferase-based HCV sub-genomic replicons of genotypes 2a (JFH-1), 1b and 3a and the compounds were assessed for their effects on both HCV replication and cellular toxicity. Initial screening of compounds was performed using the maximum non-toxic concentration and 4 compounds that exhibited a useful therapeutic index (favourable ratio of cytotoxicity to antiviral potency) were selected for extra analysis. The compounds APS (EC50 = 2.3 lM), a natural alkaloid isolated from Maytrenus ilicifolia, and the lignans 3⁄ 43 (EC50 = 4.0 lM), 3⁄ 20 (EC50 = 8.2 lM) and 5⁄ 362 (EC50 = 38.9 lM) from Peperomia blanda dramatically inhibited HCV replication as judged by reductions in luciferase activity and HCV protein expression in both the subgenomic and infectious systems. We further show that these compounds are active against a daclatasvir resistance mutant subgenomic replicon. Consistent with inhibition of genome replication, production of infectious JFH-1 virus was significantly reduced by all 4 compounds. These data are the first description of Brazilian natural compounds possessing anti-HCV activity and further analyses are being performed in order to investigate the mode of action of those compounds.
Keywords: Brazilian plants; Natural compounds; Antiviral; Hepatitis C virus; Replication